2013
DOI: 10.1016/j.critrevonc.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Breast phyllodes tumor: A review of literature and a single center retrospective series analysis

Abstract: Prognosis of phyllodes tumors is excellent. There are no convincing data to recommend any adjuvant treatment after surgery. Molecular characterization may well provide new clues to permit identification of active treatments for the rare poor prognosis cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 76 publications
11
155
3
6
Order By: Relevance
“…8 Surgical recommendations are based on a clear and reproducible inverse association between widely clear margin status and recurrence rate for malignant phyllodes tumors. [9][10][11][12][13] The definition of negative margin varies widely across authors, with some advocating a clear margin of 41 cm. 14,15 Historically, incomplete excision of any phyllodes tumors has been correlated with local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…8 Surgical recommendations are based on a clear and reproducible inverse association between widely clear margin status and recurrence rate for malignant phyllodes tumors. [9][10][11][12][13] The definition of negative margin varies widely across authors, with some advocating a clear margin of 41 cm. 14,15 Historically, incomplete excision of any phyllodes tumors has been correlated with local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal surgery with negative margin is the key to reduce incidence of local recurrence. Though radiotherapy seems to be a viable option for reducing LR, its role should be tested [40] 1999-2010 172 Benign (39.6) BT ( prospectively in a randomized setting. Patients with borderline and malignant PTs with adverse histological features (margins <1 cm irrespective of other risk factors and in the case of wide margins tumors with additional risk factors like tumor size more than 2 cm, stromal overgrowth, mitosis ≥5/HPF, stromal atypia, tumor necrosis, and elderly age) should be encouraged to participate in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a review by Spitaleri et al, it has been shown that young age (<35 years) is a poor prognostic factor for all phyllodes-related events [25] 21 (44) 6 (28.6) [32] 19 (11) 11 (57.9) in both univariate and multivariate analyses. [40] Similarly, Pandey et al reported that women over the age of 35 years showed a decreased HR (HR = 0.7). [44] However, a majority of the studies indicate advance age (>50 years) as the indicator of LR as well as survival.…”
Section: Histological Classificationmentioning
confidence: 99%
See 2 more Smart Citations